High-temperature failure in asphalt mixtures using micro-structural investigation and image analysis. (1st June 2015) - Hu, Jing; Qian, Zhendong; Liu, Yang; Zhang, Meng
Highlights: Binary images can be effectively extracted by Otsu method in different annular regions. Air-voids enlarge into a macro cracks due to horizontal movement of aggregate particles. Compressive region and shear rheological region were divided in asphalt mixture according to deformation mechanism. Size and content of coarse aggregates have significant effect on shear rheological failure. Abstract: In this study, evaluating the effect of internal structure in asphalt mixture on high-temperature deformation is the main objective. Three asphalt mixture types, dense-graded asphalt concrete, superpave and stone mastic asphalt, which widely used as pavement were selected to investigate the internal structure at meso-scale level. The internal microstructures were established by X-ray computed tomography data, and three-dimensional models were processed by digital image processing technology. Adaptive threshold segmentation algorithm based on annular regions was improved, and then utilized to extract aggregates and air-voids from gray image. Meanwhile, the morphology and distribution of air-voids and aggregates were measured. Results indicate that the improved image segmentation algorithm segregates the target and background effectively. Air-voids can be extended into a macro cracks mainly because of the horizontal shear damage, but air-voids nearby the load action area are compressed and eliminated. The content and size of coarse aggregates have an obvious influence on high-temperature failure, compressive region and shear rheological region can be divided due to the different failure mechanism. Moreover, it is found that the position changes which horizontal displacement greater than vertical displacement of aggregate particles mainly appears in shear rheological region. The method developed in this paper is an effective tool to study high-temperature failure mechanisms of asphalt mixture.